2015
DOI: 10.1136/neurintsurg-2015-011774
|View full text |Cite
|
Sign up to set email alerts
|

Stent-assisted coil embolization of aneurysms with small parent vessels: safety and efficacy analysis

Abstract: Our results suggest that SACE of aneurysms with small parent vessels is feasible in selected cases and shows good long-term patency rates of parent arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…However, in their report, Fang et al did not differentiate the individual rates for EC and SAC, which makes direct comparison difficult. Although these reported rates of retreatment are low, and all instances of retreatment included in our study were performed without further procedural related complications,2 9 17 23 24 it should not be considered that the risks of retreatment are negligible, and the risk of retreatment should also be taken into account when deciding on a treatment strategy.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, in their report, Fang et al did not differentiate the individual rates for EC and SAC, which makes direct comparison difficult. Although these reported rates of retreatment are low, and all instances of retreatment included in our study were performed without further procedural related complications,2 9 17 23 24 it should not be considered that the risks of retreatment are negligible, and the risk of retreatment should also be taken into account when deciding on a treatment strategy.…”
Section: Discussionmentioning
confidence: 88%
“…Six studies reported outcomes for unruptured aneurysms,5 9 14–17 and eight included a mix of patients with ruptured and unruptured cases 2 18–24. Twelve studies2 5 9 14 15 17–23 reported treatment outcomes exclusive to ACoA aneurysms, and two studies16 24 incorporated data on aneurysms at other locations. Documentation of the size among the treated aneurysms was highly heterogeneous among studies, and data on size was largely non-extractable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies had detailed the use of different stents, including Neuroform (Stryker Neurovascular, Kalamazoo, Michigan), Wingspan (Stryker), LEO (Balt Extrusion, Montmorency, France), and Enterprise (Codman & Shurtleff, Raynham, Massachusetts) for the treatment of wide-neck intracranial aneurysms with small vessels. [4][5][6][7][8][9] According to the previous literature, thromboembolic events or vascular occlusions are major complications of stent-assisted coiling of these aneurysms ( at follow-up. Recently, 2 low-profile self-expandable microstents, LEO Baby and LVIS Jr, were introduced.…”
Section: Discussionmentioning
confidence: 99%
“…In 44 cases treated by placement of Neuroform or Enterprise in parent arteries 2 mm or smaller in diameter, stenting was successful in 93.2%, but thromboembolism occurred in 13.6%. 8) Thus, thrombotic events tended to occur frequently after stenting of small-diameter parent arteries. Table 1 shows the recent literature concerning LVIS Jr. stent placement in peripheral vessels.…”
Section: Discussionmentioning
confidence: 99%